Risk and society - Denney, David (SAGE Publications, 2005)
What does it mean to live in 'risk society'? How does the idea of risk change how we live with each other? Risk dominates individual and collective consciousness. This book examines the social construction of risk, by considering a range of social theories, addressing the literature and providing a guide to the key issues raised.